Grundnorm, Pure Theory of Law, and Monism in the Dynamics of International Law - Samekto, FX Adji; Mahfud, Muh. Afif; Prabandari, Adya Paramita (UI Scholars Hub, 2025)
The Grundnorm is Hans Kelsen’s teaching that was integrated into his theory known as the Pure Theory of Law. The Grundnorm is the highest source of legal imperative, which is accepted by every individual human being, based on his free will to submit orders that are no longer debated because they are accepted as truth. The Grundnorm being the source of the validity of legal imperatives, it means that is the highest source of the validity of regulatory law within the scope of national and international law. This is the background of the justification of the Monism school, which is part of the teachings in the Legal-Positivism school. This paper aims to describe the relationship between The Pure Theory of Law as the basis for justifying the existence of Monism. It also seeks to answer whether Monism can still be the basis for justifying the existence of international law. The results showed that Immanuel Kant’s teaching about the developmental stages of human recognition of the universe culminated in the ratio-practical and became the source of the development of Hans Kelsen’s legal teaching on the Grundnorm. Based on Hans Kelsen’s teaching, the Grundnorm is a pre-supposed source of necessity that is formed based on free will, but it is not created through formal procedures by the state. When examined from a sociological perspective, Monism, as a doctrine in the Legal-Positivism school, presupposes the state of society that develops linearly and statically. Monism’s validity was questioned when fundamental changes occurred in state relations in the post-World War II era. These fundamental changes are further accelerated in the post-globalization era, which is based on the demand for justice in relations between states with international legal instruments.